Experimental and theoretical studies on tautomeric structures of a newly synthesized 2,2'(hydrazine-1,2-diylidenebis(propan-1-yl-1-ylidene)) diphenol - Karakurt, Tuncay; Cukurovali, Alaaddin; Subasi, Nuriye Tuna; Onaran, Abdurrahman; Ece, Abdulilah; Eker, Sitki; Kani, Ibrahim (Elsevier, 2018)
In the present study, a single crystal of a Schiff base, 2,2'(hydrazine-1,2-diylidenebis(propan-1-yl-1-ylidene)) diphenol, was synthesized. The structure of the synthesized crystal was confirmed by H-1 and C-13 NMR spectroscopic and X-ray diffraction analysis techniques. Experimental and theoretical studies were carried out on two tautomeric structures. It has been observed that the title compound studied can be in two different tautomeric forms, phenol-imine and keto-amine. Theoretical calculations have been performed to support experimental results. Accordingly, the geometric parameters of the compound were optimized by the density functional theory (DFT) method using the Gaussian 09 and Quantum Espresso (QE) packet program was used for periodic boundary conditions (PBC) studies. Furthermore, the compound was also tested for in vitro antifungal activity against Sclerotinia sclerotiorum, Alternaria solani, Fusarium oxysporum f. sp. lycopersici and Monilinia fructigena plant pathogens. Promising inhibition profiles were observed especially towards A. solani. Finally, molecular docking studies and post-docking procedure based on Molecular Mechanics-Generalized Born Surface Area (MM-GBSA) were also carried out to get insight into the compound's binding interactions with the potential. Although theoretical calculations showed that the phenol-imine form was more stable, keto-amine form was predicted to have better binding affinity which was concluded to result from loss of rotational entropy in phenol-imine upon binding. The results obtained here from both experimental and computational methods might serve as a potential lead in the development of novel anti-fungal agents. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Schiff base; tautomeric forms; AIM; Molecular docking; MM-GBSA